P56 CENTRAL PULSE PRESSURE IS ASSOCIATED WITH RETINAL ARTERIOLAR WALL THICKNESS AND WALL CROSS SECTIONAL AREA AS EVALUATED BY ADAPTIVE OPTICS - Antonio Gallo; Thomas Dietenbeck; Nadjia Kachenoura; Valérie Carreau; Michel Paques; Xavier Girerd (Artery Research, 2018)
Introduction: In 1991 Baumbach et al demonstrated taht pulse pressure (PP) but not mean arterial pressure (MAP) was correlated with pial arterioles wall cross-sectional area (WCSA)in rats. Adaptive optics (AO) allows a near-histological evaluation of retinal microcirculation (which shares the same embryological origins as the cerebral one) in a completely non-invasive fashion in humans. The aim of the study was to evaluate the relationship between PP/MAP and retinal arteriolar microcirculation. Methods: Assessment included office BP measurements realized with SphygmoCor® with the patient resting in a supine position for at least 5 minutes followed by retinal microvascular analysis with AO RTX1® Camera to measure WT, internal diameter (ID), wall-to-lumen ratio (WLR) and WCSA, realized with the patients sitting in a stable position for at least 5 minutes. Results: The study cohort consisted of 103 subjects on primary prevention and at intermediate risk, aged 20 to 80 years, with arterial hypertension and/or dyslipidemia. Study population was stratified according to median central PP (40 mmHg) and MAP (94 mmHg). Main results are shown in Table 1. Patients with a higher central PP showed an increased WT and WCSA. No difference was observed in WT and WCSA according to MAP. Conclusions: Central PP is associated with structural changes in retinal microcirculation, namely a wall thickening and an increased vascular mass, as previously found on cerebral arterioles. Adaptive Optics allows a non-invasive evaluation of a microvascular territory which shares many morphological and physiological properties with the cerebral microcirculation, representing a promising tool for the prevention of cerebrovascular events.